Exploring Other Concepts of Smart-Cities within the Urbanising Indian Context. (2016) - Varghese, Paul
Abstract: The idea of smart-cities is examined with respect to the intent, including current urbanisation models, development issues and city planning in India; the case of the proposed smart-city of Dholera in Gujarat, a flagship of proposals and current realities is looked at. An indigenous alternative following the model proposed by Dr. Abdul Kalam, of smart-villages instead is examined for appropriateness.